Medical Education Systems in China: Development, Status, and Evaluation. (9th August 2022) - Liu, Xihan; Feng, Jie; Liu, Chenmian; Chu, Ran; Lv, Ming; Zhong, Ning; Tang, Yuchun; Li, Li; Song, Kun
Abstract : Since 1949, China has made many changes to develop its medical education system and now has a complex array of medical degrees. The current system comprises a 3-year junior college medical program, 5-year medical bachelor's degree program, "5 + 3" medical master's degree program, and 8-year medical doctoral degree program; these programs each provide a different path to earning a medical degree. The advantages and drawbacks of such complexity are open to discussion. Since the government set a strategic goal of "Healthy China" in 2019, it has sought to increase the training capacity of its medical education system to establish a high-quality health service system. This article reviews medical education reform in China, discusses the current medical education system, and presents evaluations of medical education programs based on assessments by 1, 025 participants (medical students and doctors) recruited from 31 provinces of China. These assessments were compiled via a multicenter self-reported questionnaire administered July 1 to 5, 2021. Participants were training for a medical degree or practicing doctors trained in the 5-year program, "5 + 3" program, 8-year program, or "4 + 4" program. The authors assessed the medical education system to which each of the participants belong and their career stage and career satisfaction, and they requested that participants name the 3 most promising programs. The 8-year program ranked first in work satisfaction (7.92/10), education program satisfaction (7.78/10), and potential (1.91/2). Scores of the 5-year program and "5 + 3" programs were 7.25 and 7.17 for system satisfaction, respectively, and the "4 + 4" program (7.00/10) ranked the next highest. The innovations that have occurred in the Chinese medical education system have offered opportunities to meet the needs of more patients, but the lack of consistency has also posed challenges. Currently, Chinese medical education is becoming more uniform and standardized.